Greater delay discounting and cannabis coping motives are associated with more frequent cannabis use in a large sample of adult cannabis users. (1st February 2020) - Sofis, Michael J.; Budney, Alan J.; Stanger, Catherine; Knapp, Ashley A.; Borodovsky, Jacob T.
Highlights: Three latent cannabis frequency classes emerged from frequency of use measures. Greater Delay Discounting and Coping Motives related to higher frequency classes. Both may be useful treatment targets for preventing or reducing cannabis use. Abstract: Background: Self-regulation deficits expressed through a decreased ability to value future rewards (delay discounting (DD)) and impaired emotion regulation (negative urgency (NU), cannabis coping motives (CCM), and anxiety sensitivity (AS)) relate to more frequent or problematic cannabis use. However, there is a need to better understand how self-regulation and emotion regulation constructs reflect competition between deliberative and reactive systems that drive individual differences in cannabis use patterns. Further, few studies assess frequency of cannabis use within and across days of use, which may obscure differentiation of individual differences. Methods: In a large national sample of 2545 cannabis users, Latent Class Analysis was used to derive participant sub-classes based on two frequency indices, self-reported cannabis use days and times cannabis was used per day. Three classes emerged: Low (1–9 days/month, 1 time/day; 23 %), moderate (10–29 days/month, 2–3 times/day; 41 %), and high (30 days/month, ≥4 times/day; 36 %). Relationships among frequency classes and emotional regulation and impulsivity were assessed with a multinomial logistic regression. Results: Higher frequency use was associated with greater DD (χ 2 = 6.0, p = .05), greater CCM (χ 2 = 73.3, p < .001), and lower cognitive AS (χ 2 = 12.1, p = .002), when controlling for demographics, tobacco use, and number of cannabis administration methods. Frequency class and NU were not significantly associated. Conclusions: Identifying meaningful patterns of cannabis use may improve our understanding of individual differences that increase risk of frequent or problematic cannabis use. Excessive delay discounting and using cannabis to cope with negative affect may be relevant targets for treatments designed to reduce cannabis use.